Possible Major Influences of Children Learning Social Studies on Academic Self Concept and Achievement - Laurens Kaluge (Universitas Negeri Malang, 2016)
This study was aimed at finding the best model to explain pupil academic attainment in learning social studies. The data came from pupils learning Social Studies at grade 3 and 4 of primary schools. The structural equation model contained 2 exogenous constructs-attitudes toward school and locus of control-and 2 endogenous constructs-self-concept and academic achievement. It was confirmed that the academic self-concept and achievement related to each other and both were influenced by attitudes toward school and internal locus of control. The model was fitting differently for different grade.